GLOBAL DIMMING DAN MASA DEPAN PERUBAHAN IKLIM DI INDONESIA - Syamsudin, Fadli (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
A-14-year (1979-1993) image satellites of Solar Radiation, NOAA and SeaSurface Height Anomaly of TOPEX/POSEIDON and ERS-2 have been used to study a reducing solar radiation received by the Earth (global dimming) and to predict local weather anomaly for the future climate prediction in the Indonesian region. The result shows that a dimming of solar radiation is of 16.6% during 14-year observation. It is higher than the mean increasing of global dimming of 2 - 3% for every decade. This explicitly indicates that the air pollution in the form of aerosols from industrial sectors has large contributions to this this dimming process. At the other side, there is a trend of dominant warm water in the southern Jawa-Bali that affect on the increasing of rainfall intensity in the Indonesian region. We predict that flood and a longer dark during the day time, and more variative local weather change will be more frequently happen in the Indonesian region in the futu